A Participatory Action Research Study of the Collaborative Learning Process - Joseph L. Armstrong; Andrew Barrett; George W. Brutchen; Silvia Chamboneth; Jacqueline R. Stillisano (Adult Education Research Conference, 2004)
The purpose of this participatory action research project was to identify attributes that contribute to a successful collaborative learning experience. Data analysis revealed the following emergent themes to be important: reflection and dialogue, interpersonal relationships, and group and individual responsibilities.